NIGERIA’S AFRO-CENTRIC FOREIGN POLICY: AN ABERRATION IN THE PRINCIPLE AND PRACTICE OF INTERNATIONAL RELATIONS? - Nnanyere, Chukwu Ogo; Nwogbaga, David M. E. (EBSU Journal of Social Sciences and Humanities, 2024)
Nigeria got independence and qualified to conduct foreign policy as a sovereign state in 1960. At independence, Nigeria chose Africa as the centrepiece of her foreign policy. For about 50 years of Nigeria’s existence, Africa was meticulously observed as the centrepiece of her foreign policy. Against international relations principles, this choice of Nigeria’s foreign policy is an aberration in international relations. The focus of every state’s foreign policy is the interest and welfare of the state which is the centrepiece of each state’s foreign policy before the consideration of general or long-term interests – where supposedly, Africa falls within the realm of Nigeria’s national interest. From the standpoint of the realist school of thought, this research investigates if, Africa as the centrepiece of Nigeria’s foreign policy is in line with the known principles and practices of international relations. The study adopts secondary source of data collection while content analysis was deployed to distil the data collected. The findings of the research were that, given the existing circumstances in the international system as at 1960 when Nigeria gained independence vis-à-vis the bipolar nature of the system, Africa as the centrepiece of Nigeria’s foreign policy was adopted based on the leaders’ limited knowledge of the principles guiding international relations. Also, the research found out that the concept still looms large in Nigeria’s foreign policy vocabularies although the practice is no longer as it were during the Cold War and during Apartheid Policies in Southern Africa. It concludes that Africa is not supposed to be the centrepiece of Nigeria’s foreign policy because states’ central focus in international relations is their safety and the interest of her citizens as a priority before considering sub-regional, regional, or global concerns. Consequently, it is a misnomer for Africa to be the centrepiece, epic, or priority of Nigeria’s foreign policy.